2017
DOI: 10.1093/dnares/dsx026
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of Saccharomyces species inferred from completed mitochondrial genomes and revision in the ‘yeast mitochondrial genetic code’

Abstract: The yeast Saccharomyces are widely used to test ecological and evolutionary hypotheses. A large number of nuclear genomic DNA sequences are available, but mitochondrial genomic data are insufficient. We completed mitochondrial DNA (mtDNA) sequencing from Illumina MiSeq reads for all Saccharomyces species. All are circularly mapped molecules decreasing in size with phylogenetic distance from Saccharomyces cerevisiae but with similar gene content including regulatory and selfish elements like origins of replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 93 publications
(175 reference statements)
0
43
0
1
Order By: Relevance
“…Recent report suggested that the alteration of the gene order within yeast genera could be related to the mitochondrial genome size (Sulo et al 2017). While the Lachancea and Yarrowia clades, with mitochondrial genome less than 50 kb, show high synteny across species (Friedrich et al 2012;Gaillardin et al 2012), the Saccharomyces clade (mitochondrial genome size > 65 kb) is more prone to rearrangements (Sulo et al 2017). Indeed structural rearrangements were also detected in the mitochondrial genome of S. paradoxus (Yue et al 2017).…”
Section: Structural Rearrangements Are Rare In Mitochondrial Genomesmentioning
confidence: 99%
“…Recent report suggested that the alteration of the gene order within yeast genera could be related to the mitochondrial genome size (Sulo et al 2017). While the Lachancea and Yarrowia clades, with mitochondrial genome less than 50 kb, show high synteny across species (Friedrich et al 2012;Gaillardin et al 2012), the Saccharomyces clade (mitochondrial genome size > 65 kb) is more prone to rearrangements (Sulo et al 2017). Indeed structural rearrangements were also detected in the mitochondrial genome of S. paradoxus (Yue et al 2017).…”
Section: Structural Rearrangements Are Rare In Mitochondrial Genomesmentioning
confidence: 99%
“…The mitochondrial genome sequences of 128 strains in 8 Saccharomyces species (Foury et al 1998;Fritsch et al 2014;Strope et al 2015;Leducq et al 2017;Sulo et al 2017) were screened for ATP6 and ENS2 gene sequences. Evolutionary histories of these genes were inferred by using the maximum likelihood (ML) method, using MEGA6 (Tamura et al 2013).…”
Section: Mitochondrial Genome Assemblies Annotation and Phylogeniesmentioning
confidence: 99%
“…We searched the mitochondrial genome sequences of seven other Saccharomyces species (Leducq et al 2017;Sulo et al 2017) and identified ens2 sequences in Saccharomyces arboricola and Saccharomyces paradoxus ( Figure 2). Similar to S. cerevisiae ( Figure 3 and Table S6), ENS2 was located immediately downstream of ATP6 in S. arboricola (two of two strains) as well as in some S. paradoxus (9 of 25) strains; there was evidence of ENS2 introgression (Figure 1, Figure S1, and Figure S2).…”
Section: Ens2 and Atp6 Genotype-phenotype Associations And Phylogeniesmentioning
confidence: 99%
See 1 more Smart Citation
“…The intronless S. cerevisiae COX1 and S. uvarum COB alleles showed better respiratory growth at 37°C than wild-type S. cerevisiae mtDNA, suggesting a dominant negative role of introns in the hybrid. In Saccharomyces, the number and presence of mitochondrial introns is variable between species (Sulo et al 2017). This contrasts with high conservation of mitochondrial protein coding sequences, which show over 90% sequence identity between S. cerevisiae and S. uvarum, much higher than the 80% average of nuclear-encoded genes (Kellis et al 2003).…”
Section: Cyto-nuclear Interactions In Saccharomyces Evolutionmentioning
confidence: 99%